Science-gamification: Bentuk gamifikasi dan implementasi dalam pembelajaran IPA - Hasna Latipah Sakinah; Aqilatun Ni'mah; Imroatus Sulthoniyah; Dita Arisona (Universitas Garut, 2025)
Science-gamification: Forms of gamification and implementation in science learning. This study aims to identify and map the types of gamifications and their implementation in science education. Using the scoping review method, this research analyzed ten relevant scientific articles from various academic sources. The findings indicate that gamification in science learning can be classified into two main categories: application-based gamification and student activity-based gamification. Application-based gamification utilizes digital technologies such as mobile apps, interactive websites, and online quiz platforms to enhance student motivation and engagement. In contrast, student activity-based gamification relies on physical games, simulations, and active student participation in contextual and collaborative learning tasks. While both approaches show positive impacts on student involvement and conceptual understanding, each presents its own advantages and implementation challenges. This review provides a comprehensive overview of gamification trends and practices in science education and highlights opportunities for further research and the development of innovative gamified instructional strategies